THE INFLUENCE REGIONAL DEVICE UNIT WITH PERFORMANCE- BASED BUDGETING AS INTERVENING VARIABLES - Lidona, Triana (STIE Kusuma Negara, 2020)
This research examines the influence of quality of human resources, organizational commitment, improvement of administration system, communication, training or trainings on the performance of regional device work units (SKPD) through budget-based performance (ABK) as intervening variables. Research Data was obtained using questionnaire techniques to the Office of the Regional Device Unit of 37 SKPD in Mataram City West Nusa Tenggara (NTB).